Clinical performance of Determine HBsAg 2 rapid test for Hepatitis B detection. Issue 12 (27th April 2020) - Avellon, Ana; Ala, Aftab; Diaz, Antonio; Domingo, Daniel; Gonzalez, Rosario; Hidalgo, Lorena; Kooner, Paul; Loganathan, Sabarinathan; Martin, Dolores; McPherson, Stuart; Munoz‐Chimeno, Milagros; Ryder, Stephen; et al.
Abstract: Hepatitis B virus (HBV) infection is estimated to affect 292 million people worldwide, 90% of them are unaware of their HBV status. The Determine HBsAg 2 (Alere Medical Co, Ltd Chiba Japan [Now Abbott]) is a rapid test that meets European Union (EU) regulatory requirements for Hepatitis B surface antigen 2 (HBsAg) analytical sensitivity, detecting the 0.1 IU/mL World Health Organization (WHO) International HBsAg Standard. This prospective, multicentre study was conducted to establish its clinical performance. 351 evaluable subjects were enrolled, 145 HBsAg‐positive. The fingerstick whole blood sensitivity and specificity were 97.2% and 98.5% (15′ reading, reference assay cut‐off 0.05 IU/mL), sensitivity increasing to 97.9% with the prespecified cut‐off 0.13 IU/mL (EU regulations). The venous whole blood, serum and plasma sensitivity was 97.2%, 97.9%, and 98.6%, respectively (15′ reading); reaching 99%, 99.5% and 100% specificity. A testing algorithm following up an initial positive fingerstick test result with plasma/serum test demonstrates 100% specificity. The Determine HBsAg 2 test gives 15‐minute results with high sensitivity and specificity, making it an ideal tool for point‐of‐care testing, with the potential to enable large‐scale population‐wide screening to reach the WHO HBV diagnostic targets. The evaluated test improves the existing methods as most of the reviewed rapid tests do not meet the EU regulatory requirements of sensitivity. Highlights: Hepatitis B virus (HBV) is a global health problem, and up to 90% of individuals infected with hepatitis B virus worldwide are unaware of their HBV status. Hepatitis B Surface Antigen (HBsAg) is the diagnostic marker used for detection of HBV infection, and is one of the first indicators of the disease. Determine TM HBsAg 2 test is a rapid test providing an HBsAg result in 15 minutes with high sensitivity and specificity. The test meets the EU regulatory requirement for analytical sensitivity for HBsAg tests of 0.13 IU/mL, and is well placed to support the WHO diagnostic target, to diagnose 90% of HBV infected people by 2030.